2007
DOI: 10.1007/s11906-007-0094-3
|View full text |Cite
|
Sign up to set email alerts
|

Stress reduction programs in patients with elevated blood pressure: A systematic review and meta-analysis

Abstract: Substantial evidence indicates that psychosocial stress contributes to hypertension and cardiovascular disease (CVD). Previous meta-analyses of stress reduction and high blood pressure (BP) were outdated and/or methodologically limited. Therefore, we conducted an updated systematic review of the published literature and identified 107 studies on stress reduction and BP. Seventeen trials with 23 treatment comparisons and 960 participants with elevated BP met criteria for well-designed randomized controlled tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
173
2
11

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 256 publications
(193 citation statements)
references
References 44 publications
(122 reference statements)
7
173
2
11
Order By: Relevance
“…These maladaptive coping styles have long been noted in stress research to further contribute to perceived stress, as well as development or exacerbation of various chronic diseases (e.g., EH, obesity, CVD, stroke, certain cancers, etc.) (3,17). There were, however some positive coping strategies noted including taking a "time out," relaxing and exercising.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These maladaptive coping styles have long been noted in stress research to further contribute to perceived stress, as well as development or exacerbation of various chronic diseases (e.g., EH, obesity, CVD, stroke, certain cancers, etc.) (3,17). There were, however some positive coping strategies noted including taking a "time out," relaxing and exercising.…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analytic reviews have shown BAM reduces self-reported stress, anxiety, worry and their associated detrimental physiological effects including elevated blood pressure (BP) (17,18). A number of randomized clinical trials have been conducted using BAM and have indicated high acceptability, usability, and beneficial effects on stress levels, physiological functioning, and reduced casual and ambulatory BP (17,18). Our prior research has also found BAM highly acceptable, easy to learn and has resulted in reductions of stress, hostility, resting and ambulatory BP and improved sodium handling (19)(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent meta-analysis, transcendental meditation was reported to effectively lower blood pressure in patients with hypertension, whereas psychological approaches to stress management were deemed ineffective. 89 Intriguingly, the results of several studies indicate that device-guided, home-based training with slow, deep breathing can effectively reduce blood pressure in patients with hypertension, [90][91][92] although this has not been a universal finding. 93 These findings are particularly intriguing given the recent identification of an amplified bursting of SNA related to the respiratory cycle that appears to contribute to the progression and maintenance of hypertension in rats, 7 and the alterations in respiratory-sympathetic coupling recently reported in human hypertension.…”
Section: 65mentioning
confidence: 99%
“…Buoyed by the Maharishi's rise to Western fame in the late 1960's, the transcendental meditation (TM) movement predates the mindfulness movement by several decades, and appears to promote a range of health benefits ranging from lowering blood pressure to improving cognitive flexibility [16]. TM is perhaps best known in the research literature for its ability to promote relaxation and reverse physiological markers of chronic stress [17], outperforming related practices in promoting relaxation [18]. MSMT differs from TM by de-emphasizing relaxed, focus attention as a proximal goal, emphasizing instead the cultivation of awareness leading to insight into the nature of reality and one's conditioning within it [19].…”
Section: The Salutary Claimmentioning
confidence: 99%